Isolation of Phosphate Solubilizing Bacteria (PSB) from paddy field / Siti Suraiza Ramle - Ramle, Siti Suraiza (Faculty of Plantation and Agrotechnology, 2019)
Phosphorus is a second essential element after nitrogen for plant growth and development. In the soil, it is generally existing in the fixed form that will make it unavailable to plants. This study is to evaluate either there is a significant difference between using Phosphate solubilizing bacteria (PSB) that has been inoculated with Pavailability in soil or there is no significant at all. Two treatments are set up which are Merlimau soil (T0) and Merlimau soil with Phosphate Sol-ubilizing Bacteria (PSB) (T1). Parameter has being taken to measure the availability of P for the treatment and the value of soil pH. In addition, the measurement of plant height, number of tillers and the number of leaves are also being taken to discover the performance of plant growth on weekly for five weeks. When treated with the PSB, the available P and soil pH was found that it have a significant increase as shown in the result of T1 in soil analysis. Besides, the plant analysis for the plants growth also shows that the soil that have been treated with PSB is better than soil without PSB. Thus, the result also show that the plants with PSB are increasing in the height of plant, development of tillers and the leaves of plants compared to the soil that without PSB. Therefore, the application of PSB to the rice soil can enhance P availability and also can improve the growth of plant. They convert the insoluble phosphate into soluble form through the production of organic acids and make it available for plant uptake and nutrition.